1993
DOI: 10.1093/intimm/5.9.1035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the expressed B cell repertoire: role of B cell subsets

Abstract: Aged humans and experimental animals are impaired in their responses to most foreign antigens although they produce greater amounts of autoantibodies. We have examined the effect of age on the production of antibodies to a prototypic foreign antigen, sheep erythrocytes (SRBC), and to a prototypic autoantigen, bromelain-treated mouse erythrocytes (BrMRBC), in young and old mice before and after immunization with SRBC. Old mice express more anti-BrMRBC plaque-forming cell (PFC) antibodies before and an even grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
32
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 0 publications
4
32
0
Order By: Relevance
“…Consistent with studies of WT mice (20,24,25), aged 3-83␦ mice display increased numbers of splenic B cells expressing CD5. However, these cells are likely not true B1 B cells, in that they express levels of IgM equivalent to FO cells and do not express detectable levels of CD43 (data not shown).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Consistent with studies of WT mice (20,24,25), aged 3-83␦ mice display increased numbers of splenic B cells expressing CD5. However, these cells are likely not true B1 B cells, in that they express levels of IgM equivalent to FO cells and do not express detectable levels of CD43 (data not shown).…”
Section: Discussionsupporting
confidence: 75%
“…These changes include a skewing of V-gene use (20 -23), increased accumulation of CD5 ϩ B cells (24,25), and decreased inducibility of the costimulatory molecule CD86 (B7.2) (26). The latter may be attributable to age-related defects in signal transduction through the B cell Ag receptor (BCR) 3 (27,28).…”
mentioning
confidence: 99%
“…Nonetheless, several recent reports have shown intrinsic changes in the B cell pool affecting B cell responses. These include clonal expansion of CD5 ϩ B cells (48,49), impaired signal transduction events through the BCR (50), reduced inducibility of costimulatory molecules (30), and also reduced expression and activity of E2A-encoded transcription factors (herein). Moreover, it has been demonstrated that peripheral B cells from old mice are phenotypically distinct from those found in young mice and that these unique B cell populations arise and are maintained as a consequence of chronic antigenic stimulation (51).…”
Section: Discussionmentioning
confidence: 99%
“…B cell function is also diminished with age, which is in part, due to the decline in T cell production and subsequent lack of T cell help. However, there are also significant age-associated changes inherent to B cell function (20). Despite B cell numbers remaining relatively constant throughout life due to tightly regulated homeostatic mechanisms, there is a decrease in export from the bone marrow (BM) and a subsequent clonal expansion of peripheral B cells and thus a narrowing of the Ab repertoire (21).…”
mentioning
confidence: 99%
“…Decreased Ab responses to foreign Ags in the aged are thought to be primarily due to a decline in T cell help (20,22). However, defective class switching (23) and a preferential loss of high-affinity Abs may play a role (24).…”
mentioning
confidence: 99%